Cardiovascular findings in a boy with arterial tortuosity syndrome: case report and review of the literature - Ekici, Filiz; Uçar, Tayfun; Fitöz, Suat; Atalay, Semra; Tutar, Ercan (The Turkish Journal of Pediatrics, 2011)
Arterial tortuosity syndrome (ATS) is a rare hereditary, autosomal recessive, connective tissue disorder. Herein, we describe a five-year-old boy. He had hyperextensible skin, atypical facial features and inguinal hernia. We present his vascular imaging studies of kinking and tortuosity of the aorta and bilateral multiple peripheral pulmonary artery stenoses determined by conventional and magnetic resonance angiographic (MRA) examination. ATS must be considered in patients with connective tissue condition associated with diffuse arterial changes and involvement of the skin, joints and other organs. Vascular imaging studies, especially MRA, are useful in the screening of these vascular abnormalities.